Вкусная каша: стихи : [книжка-игрушка с вырубкой для дошкольного возраста] / З. Е. Александрова ; художник Н. Салиенко - Александрова Зинаида Николаевна (Малыш, читай!, 2022)
Экземпляры: Д.О. (20250317) / Инвентарный номер: 50926 / Цена: 88.00 / Авт.знак: А 46 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5